Parotid Gland Stem Cell Preservation during Intensity-Modulated Radiotherapy for Nasopharyngeal Carcinoma: Dosimetric Analysis and Feasibility. (12th July 2022) - Zheng, Lirong; Mei, Qiaoli; Gao, Yuxiang; Du, Fenglei; Xiao, Lin; Wu, Gangfeng
Abstract : Objective . Parotid gland (PG) is a radiosensitive organ, and xerostomia (XS) is a key factor affecting patients' life quality after conventional radiotherapy for head and neck tumors. In this study, dosimetry analysis was performed on PG stem cell preservation in intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC). Methods . All clinical data of 80 NPC patients diagnosed pathologically in the Radiotherapy Department of Taizhou Hospital of Zhejiang Province Affiliated with Wenzhou Medical University from August 2017 to September 2019 were retrospectively analyzed. Patients were assigned to a regular group and a restricted group according to different IMRT plans, in which a dose limitation for the parotid duct was added in the restricted group in addition to the conventional plan used in the regular group to minimize the parotid duct radiation dose. The differences in planning target volume (PTV) dose distribution, organ at risk (OAR) dose, and dose to the PG and its ducts were compared between the two groups. Results . Significantly higher mean irradiation doses of the brainstem, mandible, and oral cavity were determined in the restricted group compared with the regular group (P > 0.05 ), but there was no significant difference in the mean dose of other OARs irradiated (P > 0.05 ). As compared to the irradiation of bilateral PGs, no statistical differences were found in the mean irradiation dose and V30 between regular and restricted groups (P > 0.05 ), but lower V20 and higher V45 were determined in the restricted group (P < 0.05 ). The mean irradiation dose, V15, V20, and V26 of bilateral parotid ducts were lower in the restricted group as compared to the regular group (P < 0.05 ). Conclusion . IMRT for NPC can effectively reduce the mean irradiation dose and play a PG stem cell preservation role by giving specific dose limitation conditions to the parotid duct area without affecting PTV dose distribution and OAR irradiation dose, which has certain feasibility.